Predicting instant messenger application adoption using a unified theory of acceptance and use of technology 2 - Indrawati (2015)
In Indonesia, the average of customers in using instant messenger applications such as WhatsApp, Blackberry Messenger (BBM),LINE, KakaoTalk, and WeChat is the lowest among the South East Asia countries, but the number of application downloaded is the second highest.This condition, the second highest number of downloaded application which is not in line with highest usage of application is not good for business.The application providers should motivate customers to use the downloaded application in their activities. Analyzing factors that affect the behavior intention and usage behavior of customers toward instant messenger applications is needed.This research intends to analyze factors that affect the behavioral intention and use behavior of customers toward instant messenger applications in Indonesia, based on Unified Theory of Acceptance and Use of Technology 2.This study collected data through survey by using questionnaire distributed to Indonesian respondents, 928 valid questionnaires are analyzed by using Smart PLS 2.0. The results reveals that factors significantly influencing Behavioral Intention and Use Behavior are Habit (0.57 to Behavioral Intention and 0.37 to Use Behavior), Hedonic Motivation (0.12), Facilitating Conditions (0.11), Price Value (0.08), Effort Expectancy (0.04), and Social Influence (0.03).The R2 of Behavioral Intention is 0.65 and Use Behavior is 0.54, therefore, based on the results, the UTAUT2 model is derived to determine the Behavioral Intention and Use Behavior of consumers to use instant messenger applications in Indonesia.